An introduction to trade law and environmental law - Sinnathamby, Sri Yogamalar; Hanifa, Shamshina Mohammad (IIUM Press, 2008)
Trade Law and Environmental Law have always been hot issues at both local and international conferences. This is because they not only deal with hard economic but also man as a human being. Because human issues are involved, policies on environment and trade need to be scrutinised in order to avoid depletion of natural resources and the destruction of Mother Nature for the good of future generations.